Influence of canal water distribution system on water productivity of selected kharif crops in distributaries of Eastern Yamuna Canal (EYC) command area - Mishra, A K; Singh, Bir Pal; Sharma, R K (Recent Research in Science and Technology, 2013)
Water productivity of selected kharif season crops in the three distributaries of the Eastern Yamuna Canal Command depended on the conjunctive use of canal and ground water. Present investigations were carried out to assess the effect of water distribution on the productivity of the selected crops as well as the conjunctive use practices being followed in absence of the water in Kharif Season. It was found that in the kharif season water availability was insufficient for transplanting and irrigating paddy in the middle and tail reaches of EYC. As a result, farmers switched over from paddy to sorghum crop, thereby loosing Rs. 3075 and Rs. 3715 per ha in the middle and tail distributaries of EYC, respectively. However, the high conveyance losses resulted into lowering of the conveyance efficiencies of the three distributaries in the range of 43-44 per cent. This indicated that there lies ample scope of increasing the water availability by properly checking the seepage and evaporation losses. The balance amount of water required by crops was replenished by the ground water sources resulting into increased pressure on stored water. The water use behavior was similar in three distributaries with varying magnitude. There is a great potential of increasing food production with assured irrigation, which is currently covers about 30% of the total arable land, contributing about 56% of the total food production of the country. Present investigation established the need for increasing the conveyance efficiencies to a great extent which will result into increased culturable commands as well as adoption of better cropping patterns in the EYC command area.